Analisis Strategi Pengembangan Destinasi Wisata Museum Negeri Sumatera Selatan Balaputra Dewa Oleh Dinas Pariwisata Di Kota Palembang - Margareta, Margareta; Kencana, Novia; Febriyanti, Doris (Lembaga Penelitian dan Pengabdian Masyarakat (LPPM), Sekolah Tinggi Ilmu Sosial dan Ilmu Politik (STISIPOL) Candradimuka Palembang, 2021)
Balaputra Dewa Museum is one of the state Museums in South Sumatra province, which is grouped into 5 (five) major exhibitions and holds various kinds of collections. As for the identification of the problem of lack of facilities in promoting Museums, lack of maintenance and supervision of Museums, lack of public interest in knowing past history, lack of provision of souvenirs in Museums. This research aims to find out how the Museum's strategy of Balaputra Dewa is developed so that it can be maximized and what obstacles are faced. Data collected by the method of observation, interviews and documentation. The data analysis technique in this research is descriptive qualitative analysis. The strategy formulation stage begins with internal and external analysis. The next stage is the SWOT Matrix analysis stage. The result of the analysis shows that the national Museum development strategy of Balaputra Dewa goes into the third step of the SWOT Matrix. The alternative strategy used is a strategy that minimizes weaknesses to take advantage of opportunities (Opportunities) that must be used to minimize weaknesses and be used to reduce external threats. This strategy is the answer to research to overcome problems in the Balaputra Dewa Museum so that development in Museum can be applied optimally.